Varnost osebnih avtomobilov in interakcije med voznikom in vozilom - Žlender, Bojan (Zdravstveno varstvo, 2004)
Statistics that testify about the essential factors causing collisions and damage to cars, and injuries to people, only rarely point out defects and malfunctions of vehicles. Only as little as 1 - 2 % of accidents are ascribed to car malfunctions, and additional 5 % to a bad car condition along with a risky behaviour of a driver. However, the constantly reappearing issue is, whether certain models of vehicles are safer than other ones, and whether it is possible to discover a principle of connection between car characteristics and greater traffic safety. More than a half of all casualties in traffic are among drivers and passengers. In this paper we decided to discuss only the relation between a driver and a vehicle. A number of researchers found out, that the car mass is crucial for the safety of a driver and passengers. Greater car mass means greater safety. Despite this fact, the same car models are driven by various drivers of different age, gender, life-style, purpose ofdriving, and other features, therefore, they are involved in accidents in different ways and with different consequences.
Keywords: avtomobili; okvare; poškodbe; prometna varnost; prometne nesreče; stopnja tveganja